Faktor Determinan Keputusan Perusahaan Melakukan Transfer Pricing pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Abu Al A’la Asysyafi’i; Riyanto Setiawan Suharsono; Ari Sita Nastiti (Universitas Muhammadiyah Palembang, 2025)
This study aims to analyze the factors influencing corporate transfer pricing decisions in manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2023 period. Independent variables include taxes, bonus mechanisms, ownership structure, company size, leverage, and profitability, with transfer pricing as the dependent variable. The method used is quantitative with a multiple linear regression approach. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange in 2020–2023. The sample used was 43 companies. The results show that taxes, bonus mechanisms, and company size have a significant effect on transfer pricing decisions, while ownership structure, leverage, and profitability do not show a significant effect. These findings confirm that tax aspects and managerial incentives are the main drivers of transfer pricing practices. This study is expected to provide input for company management, tax authorities, and investors in understanding transfer pricing practices in the context of tax regulations and the capital market in Indonesia.